2016
DOI: 10.1080/10428194.2016.1205743
|View full text |Cite
|
Sign up to set email alerts
|

High non-relapse mortality and low relapse incidence in gender-mismatched allogeneic hematopoietic stem cell transplantation from a parous female donor with a male child

Abstract: To clarify the influence of exposure to a male fetus during a female donor's (FD) pregnancy in allogeneic hematopoietic stem cell transplantation (HSCT), we retrospectively examined 292 HSCT patients. The 5-year non-relapse mortality (NRM) was 33.5% among 31 male recipients who had HSCT from FD with a male child (MC), 23.0% among 40 male recipients who had HSCT from FD without MC and 19.6% among 221 other recipients. The 5-year relapse incidence (RI) was 22.6%, 42.0%, and 43.1% for the respective group. In mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In accordance to current consensus partially, HSCT using a female donor resulted in a remarkably lower relapse rate but higher survival rate in this study. Several studies had concluded that the use of a female donor, especially when the recipient is a male, was associated with reduced relapse rates [ 5 , 32 34 ]. First, the major explanation for the lower relapse rates would be the inherent information variance caused by sex chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance to current consensus partially, HSCT using a female donor resulted in a remarkably lower relapse rate but higher survival rate in this study. Several studies had concluded that the use of a female donor, especially when the recipient is a male, was associated with reduced relapse rates [ 5 , 32 34 ]. First, the major explanation for the lower relapse rates would be the inherent information variance caused by sex chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Non-relapse mortality in male patients receiving a haematopoietic stem cell transplantation from a female donor was associated with pregnancy history of the female donor, and particularly with a prior pregnancy with a male child [33]. During pregnancy, there is exchange of fetal and maternal cells across the placenta [34][35][36].…”
Section: Donor Sex and Pregnancy In Haematopoietic Stem Cell Transpla...mentioning
confidence: 99%